2006
DOI: 10.7863/jum.2006.25.5.649
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Solid Breast Masses

Abstract: Objective. The purpose of this study was to determine the reliability of sonographic American College of Radiology Breast Imaging Reporting And Data System (BI-RADS) classification in differentiating benign from malignant breast masses. Methods. One hundred seventy-eight breast masses studied by sonography with a known diagnosis were reviewed. All lesions were classified according to the sonographic BI-RADS lexicon. Pathologic results were compared with sonographic features. Sensitivity, specificity, accuracy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(33 citation statements)
references
References 23 publications
(24 reference statements)
2
27
1
Order By: Relevance
“…In our study, the most common reason for undiagnosed cancer was misinterpretation (49% [28 of 57 actionable findings]), and a noncircumscribed margin was more frequently found than in underthreshold findings (74% [42 of 57 findings] vs 40% [six of 15 findings], P = .028). Although the noncircumscribed margin is already well known for its high positive predictive value (range, 54%-82%) (20,21), lesions with this finding had not initially been US image obtained 12 months later shows that the mass (arrow) has enlarged, with a more irregular shape. This mass was confirmed as a 0.6-cm, low-grade ductal carcinoma in situ.…”
Section: Resultsmentioning
confidence: 91%
“…In our study, the most common reason for undiagnosed cancer was misinterpretation (49% [28 of 57 actionable findings]), and a noncircumscribed margin was more frequently found than in underthreshold findings (74% [42 of 57 findings] vs 40% [six of 15 findings], P = .028). Although the noncircumscribed margin is already well known for its high positive predictive value (range, 54%-82%) (20,21), lesions with this finding had not initially been US image obtained 12 months later shows that the mass (arrow) has enlarged, with a more irregular shape. This mass was confirmed as a 0.6-cm, low-grade ductal carcinoma in situ.…”
Section: Resultsmentioning
confidence: 91%
“…Other data that should be assessed include shape, margins, orientation, echotexture, posterior acoustic features, relationship with surrounding tissue, and vascularization 12. However, some carcinomas can present as probably benign lesions on ultrasonography and are generally classified as BI-RADS ® (Breast Imaging and Reporting Data System) category 3, leading to false-negative results 13,14. These lesions are usually related to specific tumor types, such as medullary, mucinous, and papillary carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…The Pearson Chi-Square test showed a p-value 0.000 which indicated that the test between the variables was statistically significant. According to Constantini the shape of the nodule is the most reliable criterion for differentiating between benign and malignant breast nodules 13 . While benign breast nodules are mostly round or oval, malignant nodules are found to be irregular in shape.…”
Section: Methodsmentioning
confidence: 99%